Save the prepuce. Painless separation of preputial adhesions in the outpatient clinic. - MacKinlay, G. A. (1988)
In most boys referred for circumcision preputial adhesions are the only problem, but these can predispose to recurrent balanitis. A simple technique using Emla cream (eutectic mixture of lignocaine and prilocaine) has been devised which allows the adhesions to be separated painlessly in the outpatient clinic. The technique was used on 39 boys aged 2 to 12 years referred for circumcision, none of whom had a retractable foreskin. The cream was applied under an occlusive dressing and left for 60 minutes before the adhesions were separated with a probe and a gauze swab. The procedure was completely pain free in 32 boys. One boy had to undergo a repeated procedure because he failed to follow the advice regularly to retract his foreskin in the three weeks after the procedure. Only one boy had to undergo circumcision later because of fibrous phimosis. In many boys referred for circumcision separation of preputial adhesions is all that is needed, and the use of this local anaesthetic technique avoids the need for general anaesthesia.